Efficacy and Outcomes of Interventional Procedures in Cancer Pain Management: A Retrospective Cohort Study - Steele, Patrick; Young, Jamie; Koh, Angelina; Ungar, Rafael; Shahzad, Eeman (Journal of Anaesthesia and Pain, 2024)
Background: Interventional procedures used for opioid-resistant cancer pain lack evidence. This study aimed to determine the effects of interventional procedures on pain, function, distress, and opioid consumption to improve the understanding of their role in cancer pain.Methods: This retrospective cohort study included 74 patients who received interventional procedures as inpatients or outpatients for cancer pain between 2021 and 2022; the primary outcomes included pain and oral morphine equivalent daily dose (oMEDD). For inpatients receiving palliative care management, the secondary outcomes were function and distress associated with pain. These were measured pre-intervention, on the day of intervention, and 3 months post-intervention. The outcomes were compared using the Wilcoxon signed-rank test with α = 0.05.Result: Most patients underwent palliative management (67.6%) and had pancreatic cancer (23.0%). In total, 94.5% of patients received temporary peripheral, neuraxial, or sympathetic blocks. Pain was most commonly experienced in the lower limbs (43.2%) and abdomen (33.8%). For the inpatients, there was a reduction in pain scores, distress, and post-intervention maintenance of function; however, these results were insignificant. Overall, the extension of oMEDD was greater in this group (p < 0.05). There was insufficient data for outpatients to assess pain, function, and distress; however, there was a decrease in regular oMEDD post-intervention (p > 0.05).Conclusion: Although interventions reduced pain, maintained function, and reduced the distress associated with pain in palliative patients, most of these results were statistically insignificant. A significant increase in inpatient oMEDD may be consistent with disease progression. Conversely, a decrease in outpatient oMEDD may suggest a more stable disease course, potentially benefiting from earlier interventions for opioid-sparing reasons.